Comparison between Online and On-Site Pre-Anesthesia Evaluation in Patients Undergoing Colonoscopy: A Randomized Controlled Trial - Soisuda Suthadsanavijit (2022)
Background: The pre-anesthesia evaluation plays a vital role to determine anesthetic risk and to plan the anesthetic technique to reduce the morbidity and mortality associated with surgery. Objective: To compare online and on-site groups for pre-anesthesia evaluation in patients undergoing colonoscopy at Surin Hospital, a tertiary care hospital in Thailand. Materials and Methods: Seventy-four patients scheduled for colonoscopy and consulted with the Surin Pre-Anesthesia Clinic (SuPAC), were randomized by a computer program and sealed envelope. Thirty-seven samples were assigned to online as the experimental group, and thirty-seven samples were assigned to on-site as the control group. The primary outcome was adequate pre-anesthesia evaluation. The authors measured pre-anesthesia checklist score to evaluate knowledge, awareness, and behavior of patients as well as comprehensive and accurate assessment before anesthesia, using 18 points. Three experts had validated these instruments. The index of item objective congruence (IOC) was 1.0, a non-inferiority test found p<0.001, and the Guttman Split-Half coefficient for reliability as internal consistency was 0.725. Secondary outcomes included the smoothness of anesthesia, incidence of postponing or canceling procedure due to inadequate preparation, complications, patient anxiety using the Thai Hospital Anxiety and Depression Scale, Thai HADS, and patient satisfaction. Results: Sixty-six patients completed the present study with 34 on-site and 32 online, with no differences in demographics data or anxiety level either before or after pre-anesthesia assessment between the two groups. The online group was significantly non-inferior pre-anesthesia evaluation than the on-site group (0.69, 95% CI 0.07 to 1.31 p=0.033, non-inferiority limit=1.0). Furthermore, the online group had a better pre-anesthesia checklist score than the on-site group at 17 (16, 18) and 16 (15.75, 17.25) points, respectively, due to the online group having more knowledge and understanding of the role of an anesthesiologist. All patients underwent a planned colonoscopy without major complications. There was no difference in patient satisfaction between groups. Conclusion: The online pre-anesthesia evaluation in Thai patients was non-inferior to the on-site evaluation, suitable in the New Normal era to allow social distancing, safe patient care, reduce the inconvenience, and reduce the cost to patients.